Combining multiple geostatistical analyses to assess the past, present, and future of fragile Mediterranean deltaic environments - Rodrigo-Comino, Jesús; Caballero-Calvo, Andrés; Almazroui, Mansour; Jiménez-Olivencia, Yolanda; Porcel, Laura; Tobias, Michelle; Nuevo-López, Abraham; Senciales-González, José María (Elsevier, 2023)
Littoral plains in general and those of the Mediterranean rivers and ramblas, are highly vulnerable territories. Understanding the past and present conditions of these areas is the best strategy to design efficient land management plans to prevent degradation such as pollutants, soil sealing, erosion, etc. in the near and medium future. In this research, different mapping techniques (land-use changes in twelve different years using manually digitalisation and field observations, from 1956 to 2019, and pattern analysis using ecological landscape indexes), multivariate statistical analyses (Spearman rank coefficient and Principal Component Analysis), and predictive models (Markov chain) are combined to assess the past, current, and future status of the Vélez River delta (Málaga province, Southern Spain), a representative vulnerable territory situated in the popular touristic area of Costa del Sol. We also included a demographic analysis using annual population census data (current inhabitants and projections) and a climate trend analysis (Mann-Kendall test) considering temperatures, precipitations and wind data. Our results demonstrate that the drastic urbanization, including new settlements, roads, and ways, has negatively impacted the delta area, even the alluvial plain, beaches, and natural sand deposits. From 1956 to 2019, >70 ha of deltaic area have been lost. The largest category of land-use, cultivated fields, accounted for up to 72.4 % of the total delta area in 1984. However, this was reduced to 41.1 % by 2019. The alluvial plain and beaches/sand deposits started from 9.3 and 11.8 %, and decreased to 5.2 and 5.9 %, respectively. Also, climate change (especially in temperature) could affect some spatial patterns. Predictive models reveal that it is likely that abandoned spaces, sand deposits, and beaches, will be transformed into new urban areas and, to a lesser extent, into cultivated fields. We concluded that the conservation of the cultivated lands...
Keywords: Ecosistemas mediterráneos; Litoral - Mediterráneo; Sistemas de información geográfica; Land spatial analysis; Land management; Mediterranean coastal ecosystem; Wetland; Geographical information systems